Immunosensors made with layer-by-layer films on chitosan/gold nanoparticle matrices to detect d-dimer as biomarker for venous thromboembolism - Rodrigues, Valquiria C.; Moraes, Marli L.; Soares, Juliana C.; Soares, Andrey C.; Sanfelice, Rafaela; Deffune, Elenice [UNESP]; Oliveira, Osvaldo N. (Oxford University Press (OUP), 2018)
We report on immunosensors to detect D-dimer, a biomarker of venous thromboembolism, which are made with layer-bylayer (LbL) films containing immobilized anti-D-dimer monoclonal antibody alternated with a layer of chitosan/gold nanoparticles (AuNpChi). Detection was due to irreversible adsorption of the antigen D-dimer on its corresponding antibody according to a Langmuir-Freundlich model, thus giving rise to ellipsoidal structures in scanning electron microscopy images whose size and number increased with D-dimer concentration. The chemical groups involved in the adsorption process were inferred from polarization-modulated infrared reflection absorption (PM-IRRAS) through changes in the amide and carbonyl bands. Detection of D-dimer was made with electrical impedance spectroscopy, electrochemical impedance spectroscopy and cyclic voltammetry. The latter was the most sensitive with a detection limit of 9 × 10-4 μg/mL, sensitivity of 0.27 × 10-6A/μgmL-1 with linear increase from 0 to 1 μg/mL. The selectivity of the immunosensor made with AuNpChi/anti-Ddimer film was verified by noting negligible changes in the cyclic voltammograms when exposed to typical interferents in biological fluids.
Keywords: D-dimer; Immunosensor; Layer-by-layer (LbL) film